Information technology and intelligent transportation systems. proceedings of the 2015 International Conference on Information Technology and Intelligent Transportation Systems ITITS 2015, held December 12-13, 2015, Xi'an China /: proceedings of the 2015 International Conference on Information Technology and Intelligent Transportation Systems ITITS 2015, held December 12-13, 2015, Xi'an China. Volume 2 : ([2017]) - Unknown
No abstract available